Implementasi Rencana Jaringan Dokumentasi dan Informasi Hukum melalui Teknologi Informasi Pemerintah Kabupaten Hulu Sungai Selatan - Rahman, Irwan (Jurnal Ilmiah Administrasi Publik, 2016)
Network Documentation and Information Law (JDIH) is outlined in the decision of the President of the Republic of Indonesia Number 91 of 1999 on the Network Documentation and Information Law National, later replaced by regulation of President of the Republic of Indonesia Number 33 Year 2012 on Network Documentation and Information National Law. Hulu Sungai Selatan government has an obligation to provide access to information to the public relating to the law of the central and local products to the wider community through the planning, implementation mechanisms and good. With open access to the public using information technology orchestrated expected government Hulu Sungai Selatan motivated to manage the documentation and legal information that is complete, accurate, easy, and fast in a network of documentation and legal information that is integrated and the integrated and work to improve service to the public by as well as possible in order to achieve the rule of law.